2020
DOI: 10.3389/fonc.2020.01740
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Prognostic Alternative Splicing Signatures in Oral Squamous Cell Carcinoma

Abstract: Background Alternative splicing (AS) plays an essential role in tumorigenesis and progression. This study aimed to develop a novel prognostic model based on the AS events to obtain more accurate survival prediction and search for potential therapeutic targets in oral squamous cell carcinoma (OSCC). Methods Seven types of AS events in 326 OSCC patients with RNA-seq were obtained from the TCGA SpliceSeq tool and the TCGA database. Cox analysis, the least absolute shrinkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Another investigation of HNSCC cell lines and tissues found MATR3, an RNA-binding protein and regulator of alternative splicing, to be upregulated in HNSCC. , Additionally, SRSF5, a splicing factor involved in constitutive splicing that can modulate the selection of alternative splice sites, has been shown to be upregulated in HNSCC tumors . Lower expression of SRSF9, another splicing factor similar to SRSF5, and RBMX, a protein implicated in alternative splicing that interacts with SRSF10, correlates with improved survival in HNSCC patients. Searching the CPTAC HNSCC data also revealed that many of these splicing-related proteins have significantly altered phosphorylation levels between HNSCC tumors and normal tissue . Two of the significantly changing phosphosites in our NOKs data set (S853 in PRPF40B and S1424 in SRRM2) were significantly changed in the same direction between tumor and normal tissue as in the NOKs and NOKs IQGAP1KO (without significant change in the proteins).…”
Section: Resultsmentioning
confidence: 99%
“…Another investigation of HNSCC cell lines and tissues found MATR3, an RNA-binding protein and regulator of alternative splicing, to be upregulated in HNSCC. , Additionally, SRSF5, a splicing factor involved in constitutive splicing that can modulate the selection of alternative splice sites, has been shown to be upregulated in HNSCC tumors . Lower expression of SRSF9, another splicing factor similar to SRSF5, and RBMX, a protein implicated in alternative splicing that interacts with SRSF10, correlates with improved survival in HNSCC patients. Searching the CPTAC HNSCC data also revealed that many of these splicing-related proteins have significantly altered phosphorylation levels between HNSCC tumors and normal tissue . Two of the significantly changing phosphosites in our NOKs data set (S853 in PRPF40B and S1424 in SRRM2) were significantly changed in the same direction between tumor and normal tissue as in the NOKs and NOKs IQGAP1KO (without significant change in the proteins).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the profile and clinical relevance of AS events in BLCA by performing a pan-cancer analysis (26). Recently, some AS bioinformatics analyses reported the good performance of AS events in predicting prognosis (27)(28)(29). However, these studies have been based on SASEs, which explains their good prognosis-predicting performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CELF2 has been identified as one of the hub splicing factors of prognostic splicing events, suggesting that these splicing factors might be used to treat glioma [84]. Moreover, in oral squamous cell carcinoma, CELF2 is identified as a promising prognostic biomarker [85].…”
Section: Celf2mentioning
confidence: 99%